A survey on farm tractor (Grabber) total cost for operation at Tridewinds Plantation Sdn. Bhd. / Muhamad Safwan Yusri Ayub - Ayub, Muhamad Safwan Yusri (Faculty of Plantation and Agrotechnology, 2019)
Farm mechanisation in Tradewinds plantation was used to minimise the labour. In Tradewinds plantation have 3000-hectare area oil palm. A survey using the secondary data last four years ago to know the total cost of operation on oil palm plantation. According to a survey for the total cost was including the fixed cost and operation cost to obtain the total cost of operation at the plantation to identify the operation cost that was including the fuel cost and maintenance cost that affects the total cost of operation. The data were collected, try to identify the factor of increasing the total cost for operation. The main factor of total cost is maintenance cost that effects the total cost of operation. All data used the Microsoft Excel to list down all cost including in operation cost since the operating cost was calculated the depreciation, tax, shelter and insurance. Based on analysis previous four years of total cost in the year 2017 is RM 38,680.03 are higher compare another year. The lower total cost in the year 2015 is RM 29,835.20 are the lower cost of operation in the plantation. However, all the total cost has a factor that affects the higher and lower total cost of operation such as the maintenance and repair cost.